Chemical analysis and characterization of biomass for biorefineries (2016)
The aim of this chapter is to offer different chemical analyses and character-ization options for researchers or whoever is looking for an appropriate methodology to analyze results obtained in laboratory tests, especially assuming the challenge to ﬁnd the best process to achieve bio-products under bioreﬁnery concept. In this way, the information provided will be very useful to evaluate the results and moreover, to improve the research process. That is the reason why analytical techniques to charac-terize different lignocellulosic biomass are described with detailed data about its prin-ciples and methodology, emphasizing either physical or chemical protocols that are followed normally in research laboratories. Taking into account that lignin, cellulose, and hemicelluloses are the principal compounds of these kinds of raw materials, which in general are residues, the information is emphasized with that target of analysis. Nevertheless, as it is possible to obtain a lot of bio-products from biomass, like sugars, alcohols, aromatics, biopolymers and so on, other analytical methods are included